Online corporate communications: website usability and content. Issue 2 (2nd May 2017) - García García, María; Carrillo-Durán, M. Victoria; Tato Jimenez, Juan Luis
Abstract : Purpose: The purpose of this paper is to establish a categorization of corporate websites as tools of online communication, in accordance with how they apply usability to the content they present, and to determine the indicators of the content and usability variables which mark the differences between each group of websites. Design/methodology/approach: The present study analyses how 754 firms manage the usability of the content they provide through the channels of their corporate websites. To this end, a cluster analysis was applied to distinguish the types of firms according to the usability and content of their websites, followed by a discriminant analysis to determine which variables differentiate the groups. Findings: The work has presented a list of the indicators that the literature has considered to be determinant aspects of firms' use of their websites for corporate strategic communications. These indicators can be applied in forming an instrument to measure the quality of company websites in this area. Originality/value: The present paper has attempted to clarify the panorama of corporate online communication via websites, understanding the issue as being not just a mere technicality but addressing it from the perspective of the emitter of the communication as a strategic instrument.